The General College Legal Paraprofessional Program An Evaluation. Volume 11, Number 2. - Minnesota Univ., Minneapolis. General Coll.; Minnesota Univ., Minneapolis. General Coll. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1974)
The General College of the University of Minnesota has a course of study for the training of legal assistants and legal administrators. In 1974 the General College Legal Paraprofessional Program was evaluated by a team of visitors representing the American Bar Association (ABA). The visitation was part of a ABA pilot project to test guidelines and procedures to be used in the future for evaluation of other para-legal programs. The first part of this document is the full text of the evaluation report submitted to the ABA by the visitation team. Before the visit of the ABA team, a self-evaluation of the program was prepared by the coordinator of the legal paraprofessional program. The visitation team relied heavily upon the text of the self-evaluation. Together the two reports provide a comprehensive description of one component of the General College paraprofessional training efforts. (Author/PG)
Educational level discussed: Higher Education.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Career Education; Higher Education; Law Schools; Lawyers; Legal Assistants; Program Descriptions; Program Evaluation; Reports, Descriptive